Self-esteem and tobacco consumption in high school adolescents - Hinojosa-García, Laura (Universidad de Sonora, 2020)
Introduction: The abuse of psychoactive substances is nowadays a public health problem closely linked to the adolescence stage due to the fact that both personality and self-esteem are not yet fully defined. Objectives: The objectives of this study are to determine the prevalence of tobacco consumption in adolescents, identify levels of self-esteem, and the relationship of the level of self-esteem with tobacco consumption. Methodology: This was a cross-sectional-descriptive and correlational study applied on a population of 900 adolescents with non-probability convenience sampling for a final sample of 324 adolescents of both genders. The Rosenberg Self-Esteem Scale and the prevalence of global, lapsic, current, and instantaneous tobacco consumption were used. Results: The average age of the participants was 13.3 years (SD = 0.99); 54% of the participants were females and 46% were males. The prevalence of tobacco consumption at some time in their life was 9.6%, while in the last month it was 1.9%. 62.3% of the adolescents were located in the high self-esteem range; with a higher percentage in male participants (70.5%), compared to female participants (55.4%). There was no significant relationship between levels of self-esteem and smoking (p> .05). Conclusions: The prevalence and frequency of tobacco consumption reported was very low. It was found that the highest percentage of participants in the study had high self-esteem.